Assessment of asthma treatment against SARS CoV-2 by using a computer approach - Hajji Halima; El Khatabi Khalil; Zaki Hanane; En-nahli Fatima; Hajji Lhossain; Lakhlifi Tahar; Ajana Mohammed Aziz; Bouachrine Mohammed (E3S Web of Conferences, 2021)
The disease caused by the coronavirus is called COVID-19. The degree of infection varies from one person to another. According to the data collected to date, people with asthma and obesity are over-represented among adults hospitalized for COVID-19. The reason is very simple: COVID-19 is a disease that particularly attacks the respiratory system, including the lungs. This pandemic has led us to return to plants. Modern medicine has found its success thanks to traditional medicine, the effectiveness of which comes from medicinal plants. Currently, in China, many people believe in the miraculous power of plants, boosting their immunity to protect against asthma. Therefore, this work aimed to study components of natural origin that have an anti-asthma effect that can be considered as the panacea against Covid-19, by using the most important method, which is molecular docking. In this research, we performed a molecular docking study on molecules naturally occurring molecules based on the recently crystallized SARS CoV-2 protein (pdb code 7C6S). ADMET prediction was performed for the selected inhibitors. The results of molecular docking and ADMET prediction support the potential of the five selected molecules to be further developed as novel inhibitors for the treatment of SARS CoV-2.